In-Depth Characterization of Somatic and Orofacial Sensitive Dysfunctions and Interfering-Symptoms in a Relapsing-Remitting Experimental Autoimmune Encephalomyelitis Mouse Model - Démosthènes, Amélie; Sion, Benoît; Giraudet, Fabrice; Moisset, Xavier; Daulhac, Laurence; Eschalier, Alain; Bégou, Mélina (Frontiers in Neurology, 2022)
Among the many symptoms (motor, sensory and cognitive) associated with multiple sclerosis (MS), chronic pain is a common disabling condition. In particular, neuropathic pain symptoms are very prevalent and debilitating, even in early stages of the disease. Unfortunately, chronic pain still lacks efficient therapeutic agents. Progress is needed (i) clinically, by better characterizing pain symptoms in MS and understanding the underlying mechanisms, and (ii) preclinically, by developing a more closely dedicated model to identify new therapeutic targets and evaluate new drugs. In this setting, new variants of experimental autoimmune encephalomyelitis (EAE) are currently developed in mice to exhibit less severe motor impairments, thereby avoiding confounding factors in assessing pain behaviors over the disease course. Among these, the optimized relapsing-remitting EAE (QuilA-EAE) mouse model, induced using myelin oligodendrocyte glycoprotein peptide fragment (35-55), pertussis toxin, and quillaja bark saponin, seems very promising. Our study sought (i) to better define sensitive dysfunctions and (ii) to extend behavioral characterization to interfering symptoms often associated with pain during MS such as mood disturbances, fatigue, and cognitive impairment, in this optimized QuilA-EAE model. We made an in-depth characterization of this optimized QuilA-EAE model, describing for the first time somatic thermal hyperalgesia associated with mechanical and cold allodynia. Evaluation of orofacial pain sensitivity showed no mechanical or thermal allodynia. Detailed evaluation of motor behaviors highlighted slight defects in fine motor coordination in the QuilA-EAE mice but without impact on pain evaluation. Finally, no anxiety-related or cognitive impairment was observed during the peak of sensitive symptoms. Pharmacologically, as previously described, we found that pregabalin, a treatment commonly used in neuropathic pain patients, induced an analgesic effect on mechanical allodynia and we showed an anti-hyperalgesic thermal effect on this model. Our results demonstrate that this QuilA-EAE model is clearly of interest for studying pain symptom development and so could be used to identify and evaluate new therapeutic targets. The presence of interfering symptoms still needs to be further characterized.